1992
DOI: 10.1111/j.1365-313x.1992.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tobacco plants expressing rgp1, a gene encoding a ras‐related GTP‐binding protein from rice, show distinct morphological characteristics1

Abstract: SummaryThe rgp7 gene, originally isolated from rice seedlings, encodes a small GTP-binding protein which is related to the product of the human proto-oncogene, ras-p21. To determine the physiological role of the rgpl protein, rgpl-p25, the coding region of rgpl was introduced into tobacco plants in both sense and antisense orientations. Transformants, which were found to contain the rgpi gene at up to three loci, showed distinct phenotypic changes. The most notable was a reduction in apical dominance with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
2
33
0
2
Order By: Relevance
“…The rumpled leaves and abnormal flower morphology seen in tobacco plants expressing a NTH15 homeobox transgene was accompanied by reduced GA 1 levels and increased levels of cytokinin (Tamaoki et al, 1997), and plants with increased cytokinin levels caused by transformation with the Agrobacterium ipt gene form ectopic buds on leaves (Estruch et al, 1991). Increased levels of cytokinin and abnormal flower development were both seen in tobacco plants expressing sense or antisense copies of a rice Rab gene (Kamada et al, 1992;Sano et al, 1994). We have confirmed that ethylene levels were perturbed in our plants, suggesting that phytohormone levels may be involved in producing at least some of the phenotypic effects in plants expressing Rab antisense transgenes as well as in those expressing homeobox genes.…”
Section: Discussionmentioning
confidence: 99%
“…The rumpled leaves and abnormal flower morphology seen in tobacco plants expressing a NTH15 homeobox transgene was accompanied by reduced GA 1 levels and increased levels of cytokinin (Tamaoki et al, 1997), and plants with increased cytokinin levels caused by transformation with the Agrobacterium ipt gene form ectopic buds on leaves (Estruch et al, 1991). Increased levels of cytokinin and abnormal flower development were both seen in tobacco plants expressing sense or antisense copies of a rice Rab gene (Kamada et al, 1992;Sano et al, 1994). We have confirmed that ethylene levels were perturbed in our plants, suggesting that phytohormone levels may be involved in producing at least some of the phenotypic effects in plants expressing Rab antisense transgenes as well as in those expressing homeobox genes.…”
Section: Discussionmentioning
confidence: 99%
“…The isopentenyl transferase gene of the Ti plasmid also induces formation of abundant shoot apices in transgenic plants (Smart et al, 1991;Smigocki, 1991;Hagen and Guilfoyle, 1992), as does the rolC gene in the Ri plasmid (Estruch et al, 1991) and the rice GTP binding protein gene (Kamada et al, 1992). Overproduction of cytokinins is thought to be the mechanism by which these genes increase the number of shoot apices and reduce apical dominance.…”
Section: Expression and Function Of Osh1 In Arabidopsismentioning
confidence: 99%
“…The rgp1 is a gene that encodes rasrelated GTP-binding protein. [29] reported that transgenic tobacco plants expressing rgp1, show different morphological characteristics. For example, some R1 progenies of selfpollinating plants developed abnormal leaf phenotypes, such as the abnormal branching of the main vein leading to the formation of twin or even triple leaves [29].…”
Section: Resultsmentioning
confidence: 99%